Understanding Virtue Ethics. - Van Hooft, Stan (Understanding movements in modern thought., 2014)
More and more philosophers have advocated varieties of virtue-based ethics that challenge moral theory traditionally founded on moral obligation and the delineation of what is right or wrong in given situations. Virtue ethics, which focuses upon the character of moral agents more than on the moral status of their actions or the consequences of those actions, has become one of the most important and stimulating areas of contemporary ethical theory. ""Understanding Virtue Ethics"" is an accessible and lively introduction to the subject. It provides a broad overview of the history of virtue ethic.